Uncoupled iron homeostasis in type 2 diabetes mellitus - Altamura, Sandro; Kopf, Stefan; Müdder, Katja; Da Silva, Ana Rita; Nawroth, Peter Paul; Muckenthaler, Martina (Journal of molecular medicine, 2017)
Diabetes mellitus is frequently associated with iron overload conditions, such as primary and secondary hemochromatosis. Conversely, patients affected by type 2 diabetes mellitus (T2DM) show elevated ferritin levels, a biomarker for increased body iron stores. Despite these documented associations between dysregulated iron metabolism and T2DM, the underlying mechanisms are poorly understood. Here, we show that T2DM patients have reduced serum levels of hepcidin, the iron-regulated hormone that maintains systemic iron homeostasis. Consistent with this finding, we also observed an increase in circulating iron and ferritin levels. Our analysis of db/db mice demonstrates that this model recapitulates the systemic alterations observed in patients. Interestingly, db/db mice show an overall hepatic iron deficiency despite unaltered expression of ferritin and the iron importer TfR1. In addition, the liver correctly senses increased circulating iron levels by activating the BMP/SMAD signaling pathway even though hepcidin expression is decreased. We show that increased AKT phosphorylation may override active BMP/SMAD signaling and decrease hepcidin expression in 10-week old db/db mice. We conclude that the metabolic alterations occurring in T2DM impact on the regulation of iron homeostasis on multiple levels. As a result, metabolic perturbations induce an "iron resistance" phenotype, whereby signals that translate increased circulating iron levels into hepcidin production, are dysregulated. KEY MESSAGES: T2DM patients show increased circulating iron levels. T2DM is associated with inappropriately low hepcidin levels. Metabolic alterations in T2DM induce an "iron resistance" phenotype.